Perception of Physical Education Teachers in the Use of Artificial Intelligence Media in the Learning Process - Syafruddin, Muhammad Akbar; Ikadarny, Ikadarny (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This study uses a qualitative approach with phenomenological design. The subjects of the study are physical education teachers from junior high school (SMP) and high school (SMA) who have experience or understanding of the use of technology, including AI-based media, in the learning process. Subjects were selected using purposive sampling techniques, which are based on certain criteria, such as having at least 3 years of experience teaching physical education, having used or having basic knowledge of AI-based media in learning, and being willing to participate in research. Qualitative data was collected through interviews. In conclusion, the use of AI technology in physical education learning has great potential to improve the quality of learning, but there are still many challenges that must be overcome. With the support of infrastructure, technological literacy, and the right policies, AI can be an important innovation that supports physical education teachers in facing the demands of the digital era.